Morphology of Ulnar Nerve and its Variation in North Indian Population - Seema Tabassum; N. B. Singh; S. K. Karn (Academia Anatomica International, 2019)
Introduction: The ulnar nerve is formed from medial cord of the brachial plexus. It lies medial to axillary and brachial artery as far as middle of humerus, and then pierces the medial  inter muscular septum  to descend on  the  anterior  face of  triceps.  Lesions of the associated structures often occur. There is anatomical variations in course of ulnar nerve amongst the races. Aim: This study was conducted to analyse the anatomical variation of ulnar nerve in north Indian population.Subjects and Methods: The study was done on 30 human cadavers at Departments of Anatomy, Darbhanga Medical College and Hospital, Laheriasarai. Results: The observations showed that-  Ulnar nerve was present in all specimens, and  in 97%  cases originated from the medial cord of the brachial plexus, at the level of tip of the acromion processes and showed the normal course. Conclusion: The awareness of  these variations along  the normal  pattern are helpful  for  the  interventional  radiologists, orthopaedicians and neurologists in preventing untoward  iatrogenic injury to the ulnar nerve during radiological procedures or operating on fractured patients or diagnostic therapy.